1992
DOI: 10.1063/1.108140
|View full text |Cite
|
Sign up to set email alerts
|

Submillimeter wave response of a high T c superconducting microbridge

Abstract: Articles you may be interested inSurface morphology effect on the photoresponse of high temperature superconducting microbridges

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
1994
1994

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…At 5 K, the 6th step at 2.2 mV was clearly present, corresponding to a Josephson oscillation above 1 THz. Only few studies on high-To junctions are found in the literature that demonstrate the AC Josephson effect up to such high voltages [1][2][3]. These studies were mainly performed with poorly reproducible devices, like point contacts [ 1 ] or thin-film bridges containing several grain-boundary junctions [2,3 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At 5 K, the 6th step at 2.2 mV was clearly present, corresponding to a Josephson oscillation above 1 THz. Only few studies on high-To junctions are found in the literature that demonstrate the AC Josephson effect up to such high voltages [1][2][3]. These studies were mainly performed with poorly reproducible devices, like point contacts [ 1 ] or thin-film bridges containing several grain-boundary junctions [2,3 ].…”
Section: Resultsmentioning
confidence: 99%
“…refs. [1][2][3]. Since most high-T¢ Josephson junctions suffer from a strong reduction of the I~Rn product as compared to the theoretical value, the question arises whether their high-frequency response is cut off at voltages above the gap voltage, as in SIS tunnel junctions [4], or already at voltages just above the l~Rn product.…”
Section: Introductionmentioning
confidence: 99%